Determinants of Banks’ Net Interest Margins in Honduras - Koffie Nassar; Edder Martinez; Anabel Pineda (Journal of Banking and Financial Economics, 2017)
This paper analyzes the determinants of banks’ net interest margins in Honduras during the years 1998 to 2013 – a period characterized by increasing banks’ net interest margins, foreign bank participation and consolidation. In line with findings in the previous literature, we find that operating costs are the most important drivers of banks’ net interest margins. We also find that competition among banks has led to higher concentration and that funding by parent banks positively impacts foreign banks’ net interest margins. Together, these results suggest that banks, particularly foreign banks, are under pressure to consolidate and reduce operating costs in order to offer competitive interest margins. We conclude that further structural reforms and consolidation may lower banks’ net interest margins.